Study on the current means of gait rehabilitation in adults with neurological pathology - Alexandra Ionela PRALĂ; Luminița Ionela GEORGESCU (Annals of the “Ştefan cel Mare” University: Physical Education and Sport Section - The Science and Art of Movement)
Introduction: Stroke causes a neurological dysfunction that leads to hemiplegia and the most serious disability is the dorsiflexion deficit that affects physiologic gait. Neurological rehabilitation represents an extremely important stage in the healing process due to the functional sequelae we encounter, sequelae of variable severity that can even cause severe handicaps. Purpose: Through this study we want to identify and highlight the therapeutic means currently used to re-educate gait in people who have suffered a stroke. We aim to find the weaknesses for the entire gait recovery process and bring new elements to the classic recovery program. Materials and methods: To carry out the study, we made an online questionnaire using the Google Forms platform and distributed it online to the target group. Results: Gait specific recovery programs are currently quite simply thought out. Currently, the greatest emphasis is on restoring the ankle joint in order to improve the dorsiflexion movement. Conclusions: We can conclude that the therapeutic strategy approached to reeducate gait at the current moment needs improvement, being largely based on the use of therapeutic physical exercises for the ankle and foot and physiotherapy and therapeutic massage procedures.